Psychological preparation of competitive judokas - A review - Ziv, G.; Lidor, R. (Journal of Sports Science & Medicine, 2013)
The purpose of this article was to review a series of studies (n = 18) on psychological preparation of competitive judokas. These studies were grouped according to the type of study performed - observational, experimental, and case studies. In addition, five psychological categories were identified: (a) imagery, (b) motivation, (c) stress, anxiety, and mood states, (d) eating attitudes and weight control, and (e) coach/athlete interactions. The main findings of this review are that (a) there is a lack of data regarding the use of imagery to improve judo performance; (b) goal involvement states of competitive judokas fluctuate and undergo abrupt changes during actual combat, according to the ecological constraints of the situation; (c) cortisol levels and somatic and cognitive anxiety tend to increase prior to and during a judo combat; (d) weight reduction programs that judokas undergo prior to a judo combat can lead to unpleasant moods, and cultural differences can lead to conflicting results; (e) psychological preparation plans should be tailored to each individual judoka, as there can be significant individual differences among the judokas. Based on the findings of our review, a number of research limitations and methodological concerns are discussed.